Complex Range Resolution Model of Point Scatterers in LFM Chirp Pulse Radar - Park, Jong Hoo; Park, Sang Chul (IEEE Transactions on Instrumentation and Measurement, 2022)
The conventional range resolution is defined as 1/bandwidth (BW). A functional range resolution is suggested as 2/BW for point scatterers. In actual radar situations, the positions of peaks do not represent actual locations of the scatterers. In addition, the amount of deviation is not proportionally decreased as the distance between the two increases. In this article, to explain and predict this situation in detail, a complex form of expression was derived in terms of the starting frequency for a linear frequency modulation (LFM) chirp pulse radar. Various range profiles of magnitude envelope were analyzed and experimented for several point targets for cases with different starting frequencies of sweep frequencies within the same bandwidth. A 'map' type of contour plot for the 'quantitative' range resolution was generated to anticipate and analyze resolution characteristics. In addition to the complex range resolution model, analyses were matched well with practical measurements.
Keywords: Chirp pulse; Computational modelling; HRR; Linear frequency modulation; Point scatterers; Quantitative resolution; Radar cross-sections; Range resolution; Resolution modeling; Signal resolution; Chirp pulse; high-resolution radar (HRR); linear frequency modulation (LFM); quantitative resolution; radar; range resolution